All land is Karbala, every day is Ashura: the pedagogy of martyrdom in Shiite narratives and the construction of an identity of resistance. 2018. Thesis (Doctorate) - Post-graduate Program in International Relations, Pontifical Catholic University of Minas Gerais, Belo Horizonte, MG - Prado, Patrícia Simone do (2018)
The aim of this thesis is to analyze how the narratives about Imam Hussein’s martyrdom in the Karbala desert in the year 680 AD may constitute a type of pedagogy among Shiites and how this can influence the construction of a type of identity between them. Structured in five chapters, this work sought to understand and interpret the construction of the Shiite identity, as a religious and political fact, based on the teaching and learning of the narrative about Imam Hussein’s martyrdom. By means of field research in Brazil and Lebanon, the objective was to verify and understand how the Shiite community teaches and learns about the martyrdom that took place in Karbala. Using the methodology of Grounded Theory and via participant observation and semi-structured interviews, the mobilizations and outcomes that the teaching of the narrative about Imam Hussein’s martyrdom generated in these communities were verified. The semistructured interviews were guided by three thematic axes: 1) the learning about Imam Hussein’s martyrdom; 2) the concept of martyrdom in Islam; 3) the importance of Imam Hussein’s martyrdom for the Shiite Muslim community and for society in general. Interviews and participant-type observations were conducted in the cities of Foz do Iguaçu, Brazil, and in Lebanon, in the city of Beirut and in the village of Mhabib. Family, religion and school were the three long-term training institutions chosen for observation and analysis about the teaching and learning of this narrative. It was interpreted that during the remembrance of Imam Hussein's martyrdom, either through the annual celebration of his martyrdom (Ashura) or through shared teaching, there is an identification with Imam Hussein’s suffering that leads to the maintenance and preservation of the values contained in the narrative. Such values are the basis for the identification of the group, religiously as Shiites and politically as resistant. It was understood in this research, that, the three institutions are responsible for teaching and maintaining this narrative, being the family the first institution to share and maintain this teaching. It can be concluded that the narratives about Imam Hussein’s martyrdom and of his companions influence the construction of a certain type of identity that presents itself both religiously and politically. Despite the different forms of teaching and comprehension of the narrative about martyrdom, it can be said that there is a common basis that allows its use as pedagogical content that feeds the construction of practices that shape specific identity/ies.